2015
DOI: 10.3324/haematol.2014.120980
|View full text |Cite
|
Sign up to set email alerts
|

Combined immunodeficiency with CD4 lymphopenia and sclerosing cholangitis caused by a novel loss-of-function mutation affecting IL21R

Abstract: Combined immunodeficiencies (CIDs) comprise a heterogeneous group of monogenic disorders manifesting with lymphocyte defects, recurrent infections and dysregulated immune response. Recently, we and others have described clinical and molecular features of the combined immunodeficiency syndromes caused by IL21 or IL21R loss-of-function mutations in humans. To date, only one homozygous mutation in the IL21 and five distinct homozygous mutations in the IL21R gene were identified, however only three have been publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 20 publications
2
29
0
2
Order By: Relevance
“…IL21R-deficient patients present with recurrent respiratory and gastrointestinal infections, including pneumonia, otitis media, and cryptosporidia, as well as reduced serum IgG levels and poor Ab responses following vaccination with TD Ags (Erman et al, 2015;Kotlarz et al, 2013Kotlarz et al, , 2014Stepensky et al, 2015; Table 1). A single IL21 patient who developed early-onset inflammatory bowel disease, recurrent respiratory infections, and hypogammaglobulinemia has also been reported (Salzer et al, 2014).…”
Section: Insights From Human Inborn Errors Of Human Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…IL21R-deficient patients present with recurrent respiratory and gastrointestinal infections, including pneumonia, otitis media, and cryptosporidia, as well as reduced serum IgG levels and poor Ab responses following vaccination with TD Ags (Erman et al, 2015;Kotlarz et al, 2013Kotlarz et al, , 2014Stepensky et al, 2015; Table 1). A single IL21 patient who developed early-onset inflammatory bowel disease, recurrent respiratory infections, and hypogammaglobulinemia has also been reported (Salzer et al, 2014).…”
Section: Insights From Human Inborn Errors Of Human Immunitymentioning
confidence: 99%
“…A single IL21 patient who developed early-onset inflammatory bowel disease, recurrent respiratory infections, and hypogammaglobulinemia has also been reported (Salzer et al, 2014). IL-21/IL-21R-deficient patients have near-normal numbers of peripheral B cells but a paucity of memory B cells, essentially lacking isotype-switched (IgG + , IgA + ) cells Erman et al, 2015;Kotlarz et al, 2013Kotlarz et al, , 2014Ma et al, 2015;Stepensky et al, 2015; Table 1). Predictably, IL-21R-deficient naive B cells failed to undergo IL-21-induced proliferation, class switching, and plasmablast differentiation in vitro due to an inability to acquire expression of AICDA, PRDM1, XBP1, and IL2RA Deenick et al, 2013; Table 1).…”
Section: Insights From Human Inborn Errors Of Human Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses of the patients P1 and P4 were defined previously [9,10]. All other patients were analyzed with NGSbased gene panel screening, which was further confirmed with Sanger sequencing as described [11].…”
Section: Genetic Analysesmentioning
confidence: 99%
“…As IL-21R -/-mice have normal B, CD4 +, and CD8 + T cell numbers as well as normal NK cell number and function, it is believed that IL-21 does not play a critical role in immune cells development. However, it was shown that these mice display a decreased number of cytotoxic T lymphocytes (CTL) and also display increased IgE and decreased IgG in response to immunization with protein antigens (22,26) Moreover, it was demonstrated that Loss-offunction mutations in the IL-21R gene cause a primary immunodeficiency syndrome which characterized by impaired IL-21-induced proliferation and immunoglobulin class-switching in B cells, cytokine production in T cells, NK cell cytotoxicity and reduction in multiple memory CD8 + T-cell subsets (27)(28)(29).…”
mentioning
confidence: 99%